2022
DOI: 10.1086/711838
|View full text |Cite
|
Sign up to set email alerts
|

Getting Conservatives and Liberals to Agree on the COVID-19 Threat

Abstract: Throughout the COVID-19 pandemic, political ideology has been perhaps the strongest predictor of consumers' perceptions of the coronavirus's threat. This article demonstrates that differences between conservatives' and liberals' responses to COVID-19 are mitigated when people perceive the virus itself to have agency. We propose that conservatives are generally more sensitive to threats that are relatively high (vs. low) in agency. Consequently, we find that greater perceived agency of the coronavirus increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Recent studies indicate that individuals' political ideology strongly influences their perceptions and acceptance of risk (Cakanlar et al,. 2020;Nowlan and Zane, 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), making it of particular importance in determining vaccine attitudes. To further test the efficacy of inoculation messaging, a second study was designed to examine the antecedents shown to influence consumer attitudes and behaviors in this context (political ideology, trust in the message source and attitude certainty).…”
Section: Study 1 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicate that individuals' political ideology strongly influences their perceptions and acceptance of risk (Cakanlar et al,. 2020;Nowlan and Zane, 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), making it of particular importance in determining vaccine attitudes. To further test the efficacy of inoculation messaging, a second study was designed to examine the antecedents shown to influence consumer attitudes and behaviors in this context (political ideology, trust in the message source and attitude certainty).…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…In their examination of the role of political ideology in consumer reaction to multiple consumption regulations (e-cigarettes, food warning labels, and using mobile phones while driving), Irmack and others (2020) found that the position held by the political party that subjects support affects how they cognitively and affectively process information presented to them about an issue. Moreover, numerous studies demonstrate that political ideology is a key contributor to individuals' attitudes about the level of threat attributed to the COVID-19 virus (Cakanlar et al, 2020;Kelly et al, 2020;Nowlan and Zane 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), as well as the efficacy of the vaccine (Bechler and Tormala, 2020;Chou and Budenz, 2020;Tyson et al, 2020).…”
Section: Political Ideologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although, it is hard to specify who exactly consumed these types of media, it can be inferred that right leaning individuals consumed right leaning media. (Motta et al 2020).¹⁰ As mentioned previously, right leaning districts did not follow public health measures, such as social distancing, as well as left leaning districts, which could have led to them having a higher number of COVID-19 cases (Gollwitzer et al 2020).¹ Right leaning individuals are less likely to wear masks because they don't feel as threatened by the virus itself (Nowlan et al 2020).¹¹ This could explain why there is less of a response from right leaning districts to those specific dates. The data, taken together, suggests that right leaning districts had a higher number of cases throughout the pandemic, and they also responded to policies and significant days of the pandemic much less.…”
Section: Interpreting the Conclusionmentioning
confidence: 98%
“…In fact, high levels of threat perception can minimize political differences in policy support between liberals and conservatives; the desire for security can override the power of partisanship (Davis & Silver, 2004;Nowlan & Zane, 2021).…”
Section: Principle 1: Spell Out Benefits Of Restricted Freedom/increased Securitymentioning
confidence: 99%